2012
DOI: 10.1161/circoutcomes.111.964668
|View full text |Cite
|
Sign up to set email alerts
|

Systems of Care for ST-Segment–Elevation Myocardial Infarction: A Report From the American Heart Association’s Mission: Lifeline

Abstract: Background— National guidelines call for participation in systems to rapidly diagnose and treat ST-segment–elevation myocardial infarction (STEMI). In order to characterize currently implemented STEMI reperfusion systems and identify practices common to system organization, the American Heart Association surveyed existing systems throughout the United States. Methods and Results— A STEMI system was defined as an integrated group of separa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
87
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 112 publications
(89 citation statements)
references
References 20 publications
0
87
0
2
Order By: Relevance
“…16 These findings are encouraging and likely underestimate the true extent of growth and development of regional STEMI systems. The survey indicated that the funding was provided by the primary PCI hospital (84%) or cardiology practice (23%) in the majority of cases.…”
Section: Growth In Regional Stemi Networkmentioning
confidence: 89%
“…16 These findings are encouraging and likely underestimate the true extent of growth and development of regional STEMI systems. The survey indicated that the funding was provided by the primary PCI hospital (84%) or cardiology practice (23%) in the majority of cases.…”
Section: Growth In Regional Stemi Networkmentioning
confidence: 89%
“…There are several barriers that have been identified that similarly may be negatively affecting patient outcomes in these community-based systems. 45 These data suggest that too many stroke centers and physicians providing advanced acute stroke therapy may actually negatively affect patient outcomes after stroke. If this is the case, how then do we rectify the need for expedient care, if only finite number of centers are available?…”
Section: Limiting the Number Of Stroke Centersmentioning
confidence: 99%
“…With programs such as the American Heart Association's Mission: Lifeline and the American College of Cardiology's Acute Coronary Treatment and Intervention Outcomes Network (ACTION) that have promoted target-vessel revascularization of patients with STEMI, a greater increase in emergency PCIs would be expected during this 5-year period. 5,6 Mission: Lifeline and ACTION may have accounted for some increase in new facilities performing PCI during this period.…”
Section: Article See P 362mentioning
confidence: 99%